PENERAPAN METODE 360 DERAJAT DAN ANALYTICAL HIERARCHY PROCESS (AHP) DALAM SISTEM PENILAIAN KINERJA PEGAWAI (STUDI KASUS : RUMAH SAKIT FADILAH PRABUMULIH) - Suzi Oktavia Kunang; Agus Bayu Samsil (Jurnal Ilmiah Matrik, 2018)
Decision support System software is very useful in the assessment process of employee performance. This study implements a method known as method name 360 degrees. This method conducts feedback evaluation by combining various feedback obtained from coworkers, employees, subordinates, officers and company customers, results of the feedback assessment process will continue with the process Assessment by using the Analytic Hierarchy Process (AHP) method which results in the decision by comparing the priority criteria so that the weight value of each criterion has been obtained by the decision. Are sorted from the largest value to the smallest. The results of the study obtained the performance value of employees in the company derived from the assessments given to all employees involved in the assessment.